MANAJEMEN KEGIATAN EKSTRAKURIKULER PRAMUKA DI SMP ISLAM AL AZHAR 12 RAWAMANGUN JAKARTA TIMUR - Supadi 1 Supadi; Evitha Soraya (Program Studi Manajemen Pendidikan, 2020)
The purpose of this study was to determine the management of the extracurricular activities of the Al Azhar 12 Islamic Middle School in Rawamangun, East Jakarta. This research uses a qualitative approach with descriptive methods. Data collection techniques are done by interview, observation, and study documentation. Data sources from this study are the Principal, Deputy Principal, Coordinator of Discipleship and Extracurricular Trustees. This research focuses on the management of scout extracurricular activities. The results of the study concluded that; (1) Scout extracurricular planning is prepared by the school principal, disciplinary coordinator and scoutmaster. The plan was prepared by referring to the existing material in the 2013 curriculum and adapted to the existing infrastructure in schools, (2) Scout extracurricular implementation is based on plans that have been made at the beginning of the learning year and also plans that have been made every week by the scoutmaster, (3) Evaluation of scout extracurricular activities is carried out in extracurricular meetings and in meetings for the preparation of learning activities which are conducted every semester. The evaluation activity involved the headmaster of the extracurricular coach and also the trainer